Translational Research for Zoonotic Parasites: New Findings toward Improved Diagnostics, Therapy and Prevention - Colella, Vito (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book is reported novel information on diagnosis, treatment, and control of parasites that are naturally transmitted from animal reservoirs to humans. Subjects: Public Health and Healthcare: Prevention; Medicine and Pharmacology: Therapy.